A Comparative Study for License Application Regulations on Proprietary Chinese Medicines in Hong Kong and Canada - Zhong, Linda L. D.; Lam, Wai Ching; Lu, Fang; Tang, Xu Dong; Lyu, Aiping; Bian, Zhaoxiang; Boon, Heather (Frontiers in Medicine, 2021)
Ethnopharmacological Relevance: Chinese Medicine plays a symbolic role among traditional medicines. As Chinese Medicine products are widely used around the globe, regulations for Chinese Medicine products are often used as models for the efficient regulation of natural products that are safe, and high-quality. Aim of the Study: We aimed to compare the regulatory registration requirements for Proprietary Chinese Medicines in Hong Kong and Canada. Materials and Methods: We compared registration requirements for Proprietary Chinese Medicine in Hong Kong and Canada based on publicly available information provided by the respective Regulators. A marketed product, Zhizhu Kuanzhong Capsule (SFDA approval number Z20020003; NPN approval number 80104354), was used as a case study to demonstrate the similarities and differences of the requirements in both Hong Kong and Canada. Results: There were similarities and differences between the two regulatory systems in terms of the quality, safety and efficacy requirements. Despite the superficial appearance of similar categories and groups/classes, Hong Kong requires significantly more primary test data compared to Canada's reliance on attestation to manufacturing according the standards outlined in approved reference pharmacopeias/texts. Conclusion: Improved understand of the similarity and differences will enable applicants to plan appropriate strategies for gaining product approval. Exploring ways to harmonize the regulatory process has the potential to benefit manufacturers, regulators, and patients by increasing efficiency and decreasing costs.